Cancer survivors' experiences of return to work: A qualitative study. Issue 10 (7th August 2018) - Zamanzadeh, Vahid; Valizadeh, Leila; Rahmani, Azad; Zirak, Mohammad; Desiron, Huget
Abstract: Objective: The study aimed to explore Iranian cancer survivors' experiences of returning to work. Methods: Semistructured interviews were conducted with 20 cancer survivors at their workplace and in a referral cancer center. Data were analyzed using a conventional content analysis technique. Results: Three main categories were identified as important in cancer survivors' experiences of returning to work: (1) individual perspectives, (2) nature of disease, and (3) access to support system. Results showed that returning to work contained different meaning for men and women. Also, it was found that cancer survivors had limited information about the disease and return to work that made them doubtful about returning to work. Conclusion: Cancer survivors have different individual perspectives that affect their decision about returning to work. Their perspectives should be assessed before returning to work, and necessary support should be provided for them in returning to work process. In this regard, health care systems and rehabilitation specialists should inform cancer survivors about the disease and return to work. Also, employers should prepare work places for cancer survivors' entrance.